Theoretical Models of Decompression-Induced Plagioclase Nucleation and Growth in Hydrated Silica-Rich Melts - Mollard, Edith; Martel, Caroline; Le Trong, Emmanuel; Rogerie, Grégory (Frontiers in Earth Science, 2020)
Microlites crystallization changes the flow properties of ascending magmas, with major implications on eruption dynamics. In order to predict microlite number density and size, we present a theoretical modelling of plagioclase nucleation and growth in rhyolitic melts, aimed at reproducing the decompression-induced isothermal crystallization experiments of Mollard et al. (2012). Thus, the modelling is valid for plagioclase crystallization in haplotonalitic/rhyolitic melts decompressed at 875 °C from 200 MPa to final pressures of 50, 75, or 100 MPa, which represents effective undercooling (Teff) of 110, 80 and 55 °C, respectively. The nucleation-rate calculation using the Classical Nucleation Theory (CNT; case of homogeneous nucleation) and values of crystal-melt interfacial tensions () either from literature or empirically calculated strongly disagree with the experimental nucleation rates. Inverting the CNT calculation by using the experimentally-determined nucleation rates suggests plagioclase-liquid from 0.041 to 0.059 J.m-2 with Teff increasing from 55 to 110 °C, which is about 2-3 times lower than  determined empirically and macroscopically. Further refining  by considering a non-smooth and non-spherical plagioclase nucleus leads to an elongated and rough morphology with a shape parameter () of 500-1350 and a rugosity parameter (ds) of 2.3. The experimental plagioclase growth rates have been modelled by atom diffusion in melt, following Fick’s second law adapted to multicomponent systems. The component with the smallest flux (i.e. limiting growth) is calcium, as determined from the analytical profiles of the experimental glasses. The crystal-growth model considers a crystal-melt interface advancing over time and a chemically-closed finite reservoir. The overall good agreement between the model and the experimental growth laws validates diffusion as the main process controlling isothermal decompression-induced plagioclase growth under moderate Teff <110 °C. The calculated CaO diffusion coefficients in silicic melt at 875 °C and water saturation pressures from 50 to 100 MPa ranges from 10-14 to 10-15 m2/s. The simulations may be relevant to predict nucleation and growth of plagioclase microlites in phenocryst-poor rhyolitic magmas that rapidly ascend from a storage zone and crystallize at shallower. This may be relevant to eruption dynamics such as dome-related blasts.